Epidemiology and Treatment Patterns of Fistulizing Crohn’s Disease in a Large, Real-World Australasian Cohort - Jack McNamara; William Wilson; Joseph L. Pipicella; Simon Ghaly; Jakob Begun; Ian C. Lawrance; Richard Gearry; Jane M. Andrews; Susan J. Connor (Gastro Hep Advances)
Background and Aims: Fistulizing Crohn’s Disease (fCD) affects up to 50% of people with Crohn’s Disease over their lifetime. Despite this high prevalence, the burden of disease, treatment and natural history in the current biologic era are poorly described. This study explores demographic, disease and treatment factors in a real-world Australasian cohort. Methods: A large real-world cohort of people with inflammatory bowel disease under routine care was interrogated in August 2023. Current fCD was defined as fistula(e) on most recent clinical, radiologic or endoscopic investigation; prior fCD was defined as the resolution of fistula(e) on most recent documentation. Results: Of 3075 people with Crohn’s Disease, 7.4% had current and 10.1% prior fCD (n = 224 & 311). Most patients were in Australia (77%), where 19.3% had current or previous fCD compared to 11% in New Zealand (P < .001). Patients with current or previous fCD were younger compared to those without (P = .003 & P < .001). Males were more commonly affected (P = .021). Current or prior fCD were more likely to be on biologic therapy (P < .001), with anti-tumor necrosis factor agents most frequently utilized. Conversely, those without fCD were more likely on Ustekinumab or Vedolizumab compared to current and prior fCD groups. People with fistulizing disease had higher hospitalization rates, while the prior fCD cohort had longer hospital admissions and more frequently required surgical intervention. Conclusion: People with fCD used more health-care resources, making this an important area for further research into care gaps to improve outcomes and optimal treatment approaches.